4 - An Alternative African Developmentalism: A Critique of Zero-sum Games and Palliative Economics - Amaizo, Yves Ekoue (Africa Development, 2021)
Africa’s economic growth and dependence since independence has been characterised by a zero-sum economic interaction with the West. This was no more than a continuation of the Centre-Periphery relationship that existed during colonial times. The result of the zero- sum game interaction between Africa and the West has been to further increase the historic unequal exchange. Economic crises marked by massive unemployment, low wages and high prices have led to dangerous migrations from the discontented continent. The problem is that the post-colonial African nations are still firmly tied to the economic theories and programmes of their erstwhile colonisers. Thus the solutions offered by way of the West are no more than palliatives. The solution is to develop new theories and pragmatic solutions that derive from autonomous Africa-centred positions. This is the significance of an alternative African developmentalism.